DDRE-43. SCREENING OF FDA-APPROVED COMPOUNDS FOR THE TREATMENT OF CHORDOMA, WITH IN VIVO VALIDATION USING THREE DIFFERENT XENOGRAFT MODELS, IDENTIFIES BRIGATINIB AS A POTENTIAL TREATMENT. (12th November 2021) - Tatman, Philip; Wroblewski, Tadeusz; Fringuello, Anthony; Scherer, Sam; Foreman, William; Damek, Denise; Youssef, Samy; Lillehei, Kevin; Ormond, David; Graner, Michael
Abstract: BACKGROUND: Chordoma is a rare malignant tumor with poor surgical control and no existing pharmacotherapies. Therefore, these tumors require additional research into novel therapeutics for their treatment. METHODS: In this study we created a high-throughput drug screen and culture system to evaluate the efficacy of existing FDA-approved compounds in 10 chordoma cell lines and primary tumors. The cell lines were graciously donated by the Chordoma Foundation. Primary tumors were collected from our operating room. In vivo validation using three separate chordoma xenograft models was also performed through the Chordoma Foundation. One model was a primary clival pediatric tumor, the second was a metastatic sacral tumor, and the third model was a recurrent skull base tumor. RESULTS: Using a 127 FDA-approved compound library, we screened 6 donated chordoma cell lines and 4 tumors resected from our institution. 5 of the chordomas were primary, 3 were recurrent, and 2 were metastatic. 6 chordoma were located in the sacrum, three were located in the mobile spine, and one was located in the clivus. Five tumors came from female patients and five came from male patients. After a single 72-hour 1um dose of brigatinib, the average tumor viability in our drug screen was reduced to 81.5% +/-9.5SD (p=1.61x10 -13 ). In the in vivo studies, brigatinib achieved a full response in the metastatic sacral chordoma xenograft model (TGI=100%, p< 0.0001), a partial response in the recurrent skull base xenograft model (TGI=54%, p=0.3048), and no response in the primary clival pediatric xenograft model (TGI = 0%, p >0.9). CONCLUSIONS: Brigatinib may be a viable treatment option for recurrent and metastatic chordomas.